Implementasi Aplikasi Identitas Kependudukan Digital (IKD) Di Disdukcapil Kota Tanjungpinang - Irma Nurdiana; Khithoh Ayumi (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2024)
This research discusses the implementation of the Digital Population Identity (IKD) application at the Disdukcapil of Tanjungpinang City in the context of E-Government. The implementation of digital identity technology as an effort to improve the efficiency of public services faces a number of challenges, including communication, resource availability, disposition, and bureaucratic structure. In terms of communication, Disdukcapil Kota Tanjungpinang uses social media and goes directly to the field to socialize and activate the IKD application. Challenges arise from people who are still unfamiliar with technology, requiring further efforts in assisting the use of the application. Resources, such as a lack of budget and dedicated teams can hinder effective implementation. Although existing teams have been empowered in the past, further attention needs to be paid to the balance of quality and quantity of human resources. The disposition of Disdukcapil officers in helping people activate IKD is positive. Within the bureaucratic structure, despite the shortage of personnel, coordination and division of labor are quite good. This research uses qualitative research methods by obtaining primary data in the form of interviews at the Tanjungpinang City Population and Civil Registration Office directly and documentation, as well as secondary data obtained from media information, the internet and other documents. In conclusion, the implementation of IKD faces several obstacles, but good communication and disposition efforts show seriousness in realizing the success of the program. Suggestions that the author can give are for the Disdukcapil of Tanjungpinang City to increase the effectiveness of implementation through strengthening communication, increasing human resources, and evaluating the bureaucratic structure on going basis.